Management Of Peenisarogam By The Siddha Physicians In Jaffna MOH Division - Thayalini, T.; Ajila, N.; Sabesan, T. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
Peenisarogam is one of the diseases related with nose, paranasal sinuses and eye in Siddha medicine. The patient with Peenisarogam suffers from the Sneezing, nasal obstruction and watery discharge. It is closely related with climate condition and allergic foods. The aim of the study was the management of peenisarogam by siddha physicians in Jaffna MOH division. A cross sectional study of Siddha physicians was done. All the physicians were interviewed by the researcher to identify the physicians who are treating Peenisarogam. 18 physicians are practicing siddha medicine in Jaffna MOH division. Out of eighteen, fourteen physicians are treating peenisarogam. All the 14 physicians were interviewed by the researcher who are treating peenisarogam. Self administrated questionnaire was used to collect the data. All the physicians (100%) mentioned hereditary and dust are the causes for the peenisam and sneezing, watery nasal discharge, irritation of the nose and itching of the eye, are the clinical features of peenisarogam. Physicians used 7 drugs in different forms to treat Peenisam. Of the 7 drugs, 2 are internal and 5 external. All 14(100%) Physicias used chooranam and head oil 5(36%) used marthirai in combination. 12(86%) Physicians used paste over the forehead, 12(86%) fumes, 12(86%) vethu and 2(14%) snuff powder as external applications. Among the 14 physicians, 9(64%) used Thalisathichooranum and 5(36%) used Punnaiverkulikai. Among the physicians used head oil, 9 (64%) used Peenisa oil and 7( 50%) Nasiroganasathaillam. Physicians treated with fumes, vethu and paste over the forehead when the patients come with heaviness of head and head ache. The peenisarogam could be compared with allergic rhinitis and conditions related with sinusitis. The finding of the study helps in recognition of effective drugs used by the physicians.
Keywords: Peenisarogam; Management; Siddha physicians